Globalization and Modernity: A Brief Discussion on Macao’s Role as a Bridgehead in Early Sino-European Cultural Exchange - SUN , Shangyang; GUO , Jianbin (Journal of Research for Christianity in China (JRCC), 2025)
The late Ming Dynasty marked an early phase of globalization, during which Macao had already become a bridge and window for cultural exchange between China and Europe. Upon arriving in the East, renowned missionaries like Matteo Ricci all landed in Macao, where they studied Chinese before venturing deeper into the interior, making significant contributions to Sino-Western cultural exchange at the time. During the persecution of the Church, Macau also provided refuge for some missionaries and believers, serving as a buffer zone for Sino-Western cultural conflicts and thereby preventing larger-scale confrontations between the two civilizations. This paper examines Macau’s pivotal role as a bridgehead in early Sino-Western cultural exchange, focusing on the cases of Matteo Ricci during the “Tolerance Period” and Alfonso Vagnone, Alvaro Semedo, and Cai Petrus during the “Prohibition Period.”